The Politics of Silencing the Narratives of Lampung Women Heroes: A Decolonial Feminist Perspective - Evi Zulvia; Rizqi Handayani; Gesit Yudha (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose This study aimed to reconstruct the silencing of narratives about Lampung's female heroes in historiography shaped by the coloniality of knowledge and patriarchy. Method This study used a qualitative approach with a literature study and critical historiography to analyze colonial archives, official Lampung history, writings about female figures, and literature on oral traditions containing collective memories about them. It employed decolonial feminist critique to examine the relationship between gender, memory politics, and local knowledge. Result/findings This study showed that Lampung's historiography produces narratives of masculine heroic figures. This was showed by a historiography that centered on male figures as heroes, while the contributions of women such as Poeti Alam Naisjah Moeloek, Putri Mentawai, Ratu Mas Lamban Gedung, and Hj. Inci Hindun Rauf were reduced, silenced, or marginalized to the domestic and cultural realms. Oral tradition needed to be seen as an alternative epistemic medium and archive preserving the collective memory of the role of female heroes outside of written colonial archives and state narratives. Conclusion This study concluded that silencing was read as a form of layered epistemic injustice between the coloniality of knowledge and the coloniality of gender. It also offered a framework to reconstruct Lampung's history in a more inclusive, gender-just manner, grounded in community knowledge.